2014
DOI: 10.1111/1754-9485.12227
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and radiobiologic comparison of 3D conformal, IMRT, VMAT and proton therapy for the treatment of early‐stage glottic cancer

Abstract: All these three modalities showed superiority with less variation among themselves compared with 3D-CRT plans. Clinical investigation is warranted to determine if these treatment approaches will translate into a reduction in radiation therapy-induced toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
0
37
0
3
Order By: Relevance
“…Several reports emphasize the dosimetric advantage of IMRT for carotid artery sparing, as carotid irradiation is well known to increase the relative risk of stroke and may limit the use of re‐irradiation if needed 13,15,38 . For example, a Surveillance, Epidemiology, and End Results (SEER)‐Medicare study showed that the 10‐year risk of cerebrovascular events for patients with head and neck cancer was 34% after conventionally delivered definitive RT vs 26% after surgery alone ( P < .01) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports emphasize the dosimetric advantage of IMRT for carotid artery sparing, as carotid irradiation is well known to increase the relative risk of stroke and may limit the use of re‐irradiation if needed 13,15,38 . For example, a Surveillance, Epidemiology, and End Results (SEER)‐Medicare study showed that the 10‐year risk of cerebrovascular events for patients with head and neck cancer was 34% after conventionally delivered definitive RT vs 26% after surgery alone ( P < .01) 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of magnetic resonance imaging for radiotherapy planning may improve tumor localization and quantification of motion during treatment [26]. For dose to the carotid PRV volumes, proton planning had superiority compared with 3D planning [27].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical stage was determined according to the American Joint Committee on Cancer staging system, 7th edition. Patients were staged using direct laryngoscopy and CT [ 9 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, carotid sparing conventional fixed-field intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) have been reported by several investigators, mainly as comparative studies based on small samples [ 2 8 9 10 11 12 13 14 15 ]. Prior treatment planning studies comparing VMAT and conventional IMRT showed that VMAT had equivocal to superior dosimetric outcomes with respect to carotid sparing [ 9 11 12 13 ]. In this study, we performed a dosimetric comparison between conventional fixed-field IMRT and VMAT to assess whether the latter was more beneficial for carotid artery sparing in the treatment of early glottic cancer.…”
Section: Introductionmentioning
confidence: 99%